Control System Design with Dead Time Compensation for a Multivariable Lime Kiln Process - Sunori, Sandeep Kumar; Juneja, Pradeep Kumar; Chaturvedi, Mayank (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945105);" role="presentation">Lime kiln is used in <span dir="ltr" style="left: calc(var(--scale-factor)*154.22px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888306);" role="presentation">numerous <span dir="ltr" style="left: calc(var(--scale-factor)*196.25px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927525);" role="presentation">pro<span dir="ltr" style="left: calc(var(--scale-factor)*209.69px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.870735);" role="presentation">cess industries such as, p<span dir="ltr" style="left: calc(var(--scale-factor)*309.53px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.863133);" role="presentation">aper <span dir="ltr" style="left: calc(var(--scale-factor)*329.47px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.06271);" role="presentation">mill<span dir="ltr" style="left: calc(var(--scale-factor)*345.31px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.875669);" role="presentation">, sugar <span dir="ltr" style="left: calc(var(--scale-factor)*374.71px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.07072);" role="presentation">mill<span dir="ltr" style="left: calc(var(--scale-factor)*390.67px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888085);" role="presentation">, cement <span dir="ltr" style="left: calc(var(--scale-factor)*427.27px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968858);" role="presentation">mill etc. <span dir="ltr" style="left: calc(var(--scale-factor)*462.58px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.969193);" role="presentation">The limekiln <span dir="ltr" style="left: calc(var(--scale-factor)*516.58px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937819);" role="presentation">is <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930799);" role="presentation">fundamentally <span dir="ltr" style="left: calc(var(--scale-factor)*132.26px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92682);" role="presentation">challenging <span dir="ltr" style="left: calc(var(--scale-factor)*181.58px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932477);" role="presentation">to <span dir="ltr" style="left: calc(var(--scale-factor)*192.05px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923976);" role="presentation">operate proficiently due to <span dir="ltr" style="left: calc(var(--scale-factor)*300.77px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938033);" role="presentation">intricate <span dir="ltr" style="left: calc(var(--scale-factor)*336.19px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899638);" role="presentation">structure <span dir="ltr" style="left: calc(var(--scale-factor)*373.87px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948482);" role="presentation">with non-<span dir="ltr" style="left: calc(var(--scale-factor)*412.39px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923697);" role="presentation">linear reactio<span dir="ltr" style="left: calc(var(--scale-factor)*465.22px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910602);" role="presentation">n kinetics, and <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907525);" role="presentation">large dead time<span dir="ltr" style="left: calc(var(--scale-factor)*134.42px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.04814);" role="presentation">. It <span dir="ltr" style="left: calc(var(--scale-factor)*149.06px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923294);" role="presentation">turns out to be <span dir="ltr" style="left: calc(var(--scale-factor)*210.89px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869279);" role="presentation">dangerous <span dir="ltr" style="left: calc(var(--scale-factor)*254.81px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0636);" role="presentation">if it is <span dir="ltr" style="left: calc(var(--scale-factor)*281.93px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929484);" role="presentation">functioned <span dir="ltr" style="left: calc(var(--scale-factor)*327.79px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895532);" role="presentation">outside <span dir="ltr" style="left: calc(var(--scale-factor)*359.59px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920031);" role="presentation">the set points. So, the automation of this <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895995);" role="presentation">process is very <span dir="ltr" style="left: calc(var(--scale-factor)*134.06px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.981882);" role="presentation">critical <span dir="ltr" style="left: calc(var(--scale-factor)*164.42px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930748);" role="presentation">for optimization of product quality, product rate and e<span dir="ltr" style="left: calc(var(--scale-factor)*380.59px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941491);" role="presentation">conomy. <span dir="ltr" style="left: calc(var(--scale-factor)*417.91px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905797);" role="presentation">The current research work <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*387.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935282);" role="presentation">deals with <span dir="ltr" style="left: calc(var(--scale-factor)*116.66px); top: calc(var(--scale-factor)*387.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.984756);" role="presentation">a 2x2 lim<span dir="ltr" style="left: calc(var(--scale-factor)*155.78px); top: calc(var(--scale-factor)*387.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.978614);" role="presentation">e kiln model. H<span dir="ltr" style="left: calc(var(--scale-factor)*220.37px); top: calc(var(--scale-factor)*387.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959628);" role="presentation">aving done its multivari<span dir="ltr" style="left: calc(var(--scale-factor)*317.71px); top: calc(var(--scale-factor)*387.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91343);" role="presentation">able analysis, its decoupling has been <span dir="ltr" style="left: calc(var(--scale-factor)*474.34px); top: calc(var(--scale-factor)*387.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878142);" role="presentation">done. <span dir="ltr" style="left: calc(var(--scale-factor)*499.54px); top: calc(var(--scale-factor)*387.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935364);" role="presentation">Using <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*400.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.989738);" role="presentation">MATLAB, dead <span dir="ltr" style="left: calc(var(--scale-factor)*140.90px); top: calc(var(--scale-factor)*400.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920675);" role="presentation">time compensation is done with smith predictor design <span dir="ltr" style="left: calc(var(--scale-factor)*364.03px); top: calc(var(--scale-factor)*400.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904375);" role="presentation">and its <span dir="ltr" style="left: calc(var(--scale-factor)*393.31px); top: calc(var(--scale-factor)*400.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905657);" role="presentation">performance is compared to that <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*413.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00562);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*82.82px); top: calc(var(--scale-factor)*413.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910513);" role="presentation">control system without dead time compensation